Low-Tech Design-Based Learning in the Female Student Leadership Organization at Ibnul Qoyyim Putri - Kartika Ayu Prasetyo; Naufal Ahmad Rijalul Alam (Journal of Islamic Education Students (JIES), 2026)
This study aims to identify and describe the leadership learning process of female students in the OSIQ organization at Ibnul Qoyyim Putri Islamic Boarding School and to examine its alignment with the stages of low-tech Design-Based Learning (DBL). This research employed a qualitative case study approach. Data were collected through in-depth interviews and observations involving core administrators, division administrators, and female student supervisors. Data were analyzed through data reduction, data display, and conclusion drawing, supported by source triangulation to ensure validity. The findings indicate that leadership learning occurs contextually through active involvement in organizational activities. Students identify problems, design solutions through deliberation, implement decisions directly, and conduct reflection for continuous improvement. These practices implicitly reflect the stages of low-tech DBL. Open communication, teamwork, collective decision-making, and mentoring from supervising teachers strengthen leadership development. This study contributes theoretically and practically by providing an empirical description of female student leadership learning patterns within an Islamic boarding school context.